2018
DOI: 10.2139/ssrn.3121352
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education on Family Formation: Quasi-Experimental Evidence from the UK

Abstract: We thank Julie Jefferies and Louise O'Leary for the considerable time and effort that they and their team have devoted to this project. It would not have been possible without the live births dataset that they supplied. We also thank Mary Grinsted for generously supplying the abortion data used in this paper and Kevin Lynch for his help with the Longitudinal Study. We are extremely grateful to Damon Clark for his invaluable input and help in securing the data. Thanks to various seminar participants, Sarah Bana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 59 publications
(94 reference statements)
5
24
0
Order By: Relevance
“…Overall, while our findings confirm the hypothesis that education reduces fertility using the 1947 reform in England, we have to reject this hypothesis for Continental Europe. As described in Section 1, Monstad et al (2008), Fort (2009) and Geruso and Royer (2014) found no significant effects of education induced by mandatory schooling in Norway, Italy and the 1972 reform in the UK on total fertility. 19 Leon (2004) found a negative impact of education on fertility of around À0.33 and a small positive effect on childlessness for the US.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Overall, while our findings confirm the hypothesis that education reduces fertility using the 1947 reform in England, we have to reject this hypothesis for Continental Europe. As described in Section 1, Monstad et al (2008), Fort (2009) and Geruso and Royer (2014) found no significant effects of education induced by mandatory schooling in Norway, Italy and the 1972 reform in the UK on total fertility. 19 Leon (2004) found a negative impact of education on fertility of around À0.33 and a small positive effect on childlessness for the US.…”
Section: Discussionmentioning
confidence: 79%
“…Monstad et al (2008) studied completed fertility and timing of births in Norway, Fort (2009) investigated Italy, Braakmann (2011) and Geruso and Royer (2014) looked at the United Kingdom and Cygan-Rehm and Maeder (2013) examined Germany. Monstad et al (2008), Fort (2009) and Geruso and Royer (2014) find evidence of a postponement of childbearing away from the teenage years but no significant effects on total fertility. 2 Conversely, Braakmann (2011) detects a positive causal effect of education on the number of children and Cygan-Rehm and Maeder (2013) find a negative effect on the number of children and a positive effect on childlessness.…”
Section: Education and Fertilitymentioning
confidence: 99%
“…This timing, significantly after the completion of primary school, reduces the possibility of an incarceration effect driving the results. A remaining concern is that postponements of early fertility decisions tend to be replaced by additional births at later ages (Black et al, 2008;Geruso and Royer, 2018). However, the reforms in Ethiopia have a greater negative effect on fertility at each subsequent age from 22 through 29; the evidence suggests that the reduction in fertility actually increases as women age.…”
Section: National Results With Consideration Of Mother Tongue Instrucmentioning
confidence: 99%
“…However, a number of other papers in the recent literature find evidence of an initial delay in fertility, but no change in total fertility (Black et al, 2008;Monstad et al, 2008;Fort, 2012;Geruso et al, 2014), and the 3 previously mentioned paper by Fort et al (2016) finds a positive causal relationship between schooling and fertility in continental Europe and a negative relationship in the UK. This literature finds surprisingly mixed results, suggesting the need for a greater understanding of the linkages between schooling and fertility.…”
Section: Introductionmentioning
confidence: 94%